(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
Many language students struggle with listening because it’s essential to communicate. This research aimed to examine how ESL students used metacognitive strategies to improve their listening comprehension while preparing for the International English Language Testing System (IELTS). In this study, semi-structured interviews were utilized as a research tool to explore how chosen participants employed metacognitive strategies to improve their listening comprehension in preparation for the International English Language Testing System (IELTS). Ten undergraduate students were interviewed for this study; they had all participated in an intervention program to teach them metacognitive strategies for improving their listening. We recorded and transcribed the semi-structured interviews and used a coding system to analyze the data. Although most people of average intelligence engage in metacognitive regulation when presented with an effortful cognitive task, the results of this study suggest that some people are more metacognitive than others, implying that metacognitive strategies give a viable solution for acquiring appropriate skills in the listening component. Successful academic performance is typically associated with high levels of metacognition. Students were open to the new methods and gained self-assurance due to their improved ability to study independently. Therefore it also had a favorable effect on their learning habits. Using metacognitive tactics to help students of all skill levels improve their English listening is an area with much-untapped promise